2019
DOI: 10.1039/c9nr06609h
|View full text |Cite
|
Sign up to set email alerts
|

An in-plane Co9S8@MoS2 heterostructure for the hydrogen evolution reaction in alkaline media

Abstract: MoS2/Co9S8 heterostructures were in situ grown on three-dimensional carbon network substrates with interconnected hierarchical pores, exhibit excellent alkaline HER activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…A similar change of slope is also observed in the case of polycrystalline silver [17] and may indicate a change in HER mechanism [15]. In the case of Au surfaces, the catalytic activity follows a different sequence compared to Pt: Au(111) > Au(100) > Au (110) (Table 1), while the Tafel slope varies gradually from about −60 mV dec −1 at low overpotentials to −120 mV dec −1 at high overpotentials (in about the same Since the highest |j 00 | is exhibited by Pt, atomic-scale studies of HER rate dependence on the Pt single crystal surfaces' atomic-scale morphology have been in the research focus for years. Marković et al [14] have first demonstrated that HER in acid solutions is a surface-sensitive process, i.e., that its rate depends on the Pt crystal orientation, as can be clearly seen in Figure 2, left.…”
Section: Her At Single Crystal Surfaces and Bulk Surfacessupporting
confidence: 67%
See 1 more Smart Citation
“…A similar change of slope is also observed in the case of polycrystalline silver [17] and may indicate a change in HER mechanism [15]. In the case of Au surfaces, the catalytic activity follows a different sequence compared to Pt: Au(111) > Au(100) > Au (110) (Table 1), while the Tafel slope varies gradually from about −60 mV dec −1 at low overpotentials to −120 mV dec −1 at high overpotentials (in about the same Since the highest |j 00 | is exhibited by Pt, atomic-scale studies of HER rate dependence on the Pt single crystal surfaces' atomic-scale morphology have been in the research focus for years. Marković et al [14] have first demonstrated that HER in acid solutions is a surface-sensitive process, i.e., that its rate depends on the Pt crystal orientation, as can be clearly seen in Figure 2, left.…”
Section: Her At Single Crystal Surfaces and Bulk Surfacessupporting
confidence: 67%
“…A similar change of slope is also observed in the case of polycrystalline silver [17] and may indicate a change in HER mechanism [15]. In the case of Au surfaces, the catalytic activity follows a different sequence compared to Pt: Au(111) > Au(100) > Au (110) (Table 1), while the Tafel slope varies gradually from about −60 mV dec −1 at low overpotentials to −120 mV dec −1 at high overpotentials (in about the same The dependency of the HER rate on the crystallographic orientation of the electrode was also demonstrated for the case of silver [15] and gold [16] in acid solutions. While the Tafel plots for Ag (111) were found to be linear, in the case of Ag(110) they exhibit a distinct slope change.…”
Section: Her At Single Crystal Surfaces and Bulk Surfacessupporting
confidence: 67%
“…In addition, Fig. S9 shows that the Tafel slope of NiBi/GDY was 156.1 mV dec −1 , lower than that of NiBi (298.0 mV dec −1 ), demonstrating that the Volmer step was rate-determining and that rapid HER kinetics were realized in NiBi/GDY by accelerating the Volmer reaction [42]. The excellent HER performance of NiBi/GDY was possibly due to the strong coupling between NiBi and GDY, the latter of which significantly improves the conductivity of NiBi/GDY.…”
Section: Resultsmentioning
confidence: 96%
“…Other works focused on preparation of HER active chalcogenides and hydroxides include Ni-Co sulfide/Ni-Co carbonate-hydroxide grown on Ni foam [95], MoS2@Ni(OH)2/Ni foam [96], Co9S8@MoS2 [97], Te@NiTe2/NiS [98], MoS2 coated Ni3S2 [99], WS2 supported on TiO2 [100], N-doped reduced graphene oxide supported CoSe2 [101], Co9S8 supported on N,S co-doped carbon [102], MoNiS@NiS [103], Mo-incorporated Ni(OH)2 [104], Ni2P-NiSe2 [105], NiCo2S4/CdO [106], Ni3S2 decorated by Ni3Sn2S2 quantum dots [107], metallic WSe2:Sn supported on reduced graphene oxide [108], and RuO2/Co3O4-RuCo supported on N-doped carbon [109].…”
Section: Supported Chalcogenides Hydroxides Pnictides and Carbidesmentioning
confidence: 99%